Improved Charge-Trapping Performance of Hf-Doped SrTiO3 for Nonvolatile Memory Applications. (27th March 2015) - Huang, X.D.; Lai, P.T.
Abstract : The charge-trapping characteristics of Hf doped SrTiO3 have been studied based on Al/Al2O3/Hf-doped SrTiO3 /SiO2 /Si capacitors. The thermodynamic stability of the SrTiO3 film is significantly improved by Hf incorporation, thus resulting in negligible formation of an interlayer at the Hf-doped SrTiO3 /SiO2 interface, as confirmed by X-ray photoelectron spectroscopy and transmission electron microscopy. The memory device with Hf-doped SrTiO3 as charge-trapping layer displays high speed at low operating voltage (a VFB shift of 1.9 V at +6 V, 100 ms) and good data retention (charge loss of 12.7% after 10 4 s). Therefore, the Hf-doped SrTiO3 film is a promising material as charge-trapping layer for high-performance nonvolatile memory applications.